2014
DOI: 10.1007/978-3-319-08019-2_16
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Life as Cognitive Info-computation

Abstract: Abstract. This article presents a naturalist approach to cognition understood as a network of info-computational, autopoietic processes in living systems. It provides a conceptual framework for the unified view of cognition as evolved from the simplest to the most complex organisms, based on new empirical and theoretical results. It addresses three fundamental questions: what cognition is, how cognition works and what cognition does at different levels of complexity of living organisms. By explicating the info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Therefore, we are forced to adopt a physical interpretation of the transport of information that cannot rest only on the role of crucial events. Nevertheless, we think that this paper affords an important contribution to the revolution occurring in biology [1,3,4]. This is so because, first of all, to the best of our knowledge, in the current literature no research work has revealed the existence of crucial events in germination processes.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, we are forced to adopt a physical interpretation of the transport of information that cannot rest only on the role of crucial events. Nevertheless, we think that this paper affords an important contribution to the revolution occurring in biology [1,3,4]. This is so because, first of all, to the best of our knowledge, in the current literature no research work has revealed the existence of crucial events in germination processes.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, the single cell itself is an intelligent system and the brain should not be interpreted as a supercomputer but rather as "an entire community of supercomputers " [3]. Gordana Dodig-Crnkovic [4] points out that although until recently intelligence was considered a property of human beings, but now due to the autopoiesis of Maturana and Varela [5] cognition should be extended to all biological systems. This observation has the impressive effect of marking the breakdown of separation between different disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the self-referential frame, any assessment of information is a measurement [ 38 , 39 ]. Self-referential cells are cognitive and must actively evaluate sensory information to sustain their homeostatic equipoise [ 21 , 22 , 23 , 83 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. Cognitive cells must measure since their sensory information is imprecise.…”
Section: The N-space Episenome As An Informational Matrix For Suprmentioning
confidence: 99%
“…Maturana and Varela were the first to propose that the life itself can be understood as a process of cognition [32,33]. Building on Maturana and Varela's understanding of cognition the author proposed an infocomputational constructive framework [18,[34][35][36][37] with the aim to explain how increasingly complex structures develop as a result of information processing in nature. These information processes can be modeled as natural morphological computation, in the network of networks of physical processes where constant exchange (communication) of data (signals) among agents establishes new structures on physical, chemical and biological levels.…”
Section: Morphological Infocomputation In Cognitive Systemsmentioning
confidence: 99%